1987
DOI: 10.1161/01.cir.76.5.1110
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent claudication, exercise, and blood rheology.

Abstract: Forty-two stable patients with claudication were assigned to two groups. Group I (n 22) was submitted to regular, standardized treadmill exercise for 2 months. During this time the maximal and pain-free walking distances increased significantly (more than 100%

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(43 citation statements)
references
References 24 publications
0
43
0
Order By: Relevance
“…Even doing easy exercises we would expect to see an increase in blood viscosity due to the fact that exercise stimulates an inflammatory response [12] [28] [44] [45]. This response can increase the number of free radicals that could cause the red blood cells to lose some of their negative charge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even doing easy exercises we would expect to see an increase in blood viscosity due to the fact that exercise stimulates an inflammatory response [12] [28] [44] [45]. This response can increase the number of free radicals that could cause the red blood cells to lose some of their negative charge.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier work has demonstrated the short and long-term effects of exercise on blood viscosity [43]- [45]. The short-term effect is an increase in blood viscosity [46], a function of duration and intensity of exercise, viability of the capillaries, red blood cell deformation characteristics, hematocrit and state of hydration.…”
Section: Exercise and Blood Viscositymentioning
confidence: 99%
“…Another recent randomised trial of a statin also observed increased walking ability of claudicants [9], possibly due to reduced blood viscosity [10]. Finally, regular exercise (walking) may increase the walking ability of claudicants partly through reductions in fibrinogen and viscosity [11][12][13].…”
Section: Flow Atherogenesis and Chronc Ischaemiamentioning
confidence: 99%
“…In addition, a strong association between fibrinogen, coronary events and thrombotic stroke has been observed in a number of large epidemiologic studies, including Göte borg [31], Caerphilly [32], Speedwell [33], Framingham [34], and Northwick Park [35], Several reports suggest that increased plasma viscosity and abnormalities in blood rheology occur commonly in patients with renovascular and essential hypertension [36][37][38], hypertensive heart disease [39,40], and peripheral vascular disease [41][42][43][44],…”
Section: Plasma and Whole Blood Viscositymentioning
confidence: 99%